2017
DOI: 10.21831/amp.v5i2.7480
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas manajemen praktik kerja industri di Sekolah Menengah Kejuruan Kota Yogyakarta

Abstract: Penelitian ini bertujuan: (1) mengevaluasi keefektifan manajemen praktik kerja industri di SMK, (2) menganalisis kendala yang ada pada manajemen praktik kerja industri di SMK. Penelitian ini merupakan penelitian evaluasi dengan pendekatan kuantitatif. Teknik pengumpulan data menggunakan angket. Analisis data menggunakan teknik persentase. Hasil penelitian ini menunjukkan bahwa aspek perencanaan pada manajemen praktik kerja industri (prakerin) memiliki kriteria sangat efektif. Aspek pelaksanaan pada manajemen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…[5] explained that the partnership model of SMK-DUDI is expected to be a collaboration that can facilitate the development of professional competence and bridge the competency gap of SMK graduates with the need of job market. The results of [13] showed that the overall effectiveness of Prakerin management in SMK Kota Yogyakarta has very effective criteria. Aspects of planning and execution resulted in high gap points, namely: (1) the Prakerin group officials in schools are less than four persons, (2) the business world and the industrial world around the school are not always relevant to the program (4) the relevance of the teacher counsellors' skill program with the underguided students, (5) the implementation of the scheme is still often hampered by student discipline, (6) the working group still finds Prakerin participants who completed their Prakerin activities did not match the time allocation.…”
Section: Partnership Design Of Smk and Dudimentioning
confidence: 98%
“…[5] explained that the partnership model of SMK-DUDI is expected to be a collaboration that can facilitate the development of professional competence and bridge the competency gap of SMK graduates with the need of job market. The results of [13] showed that the overall effectiveness of Prakerin management in SMK Kota Yogyakarta has very effective criteria. Aspects of planning and execution resulted in high gap points, namely: (1) the Prakerin group officials in schools are less than four persons, (2) the business world and the industrial world around the school are not always relevant to the program (4) the relevance of the teacher counsellors' skill program with the underguided students, (5) the implementation of the scheme is still often hampered by student discipline, (6) the working group still finds Prakerin participants who completed their Prakerin activities did not match the time allocation.…”
Section: Partnership Design Of Smk and Dudimentioning
confidence: 98%
“…The poor quality of graduates is a significant issue in the field of vocational education (Kokom et al, 2020). The current vocational education process is still not integrated with stakeholders from industries and other organizations (Syahyadi, 2020), and practices in vocational education institutions with industries that are not yet relevant (Permana & Sukoco, 2017). The WBL model that is being used is still quite repetitive, and there paperASIA 39 (6b): 2023 132 is no such thing as autonomous learning that takes place on campus (Sebayang et al, 2017;Hastuti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%